Living Laws in Forest Guarding in Aceh Portrait of Experiences Past and Today - Suganda, Delfi (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2024)
Forests are an important element in the life dimensions of the Acehnese people. There are several important things about forests for the people of Aceh. Firstly, forests are the people of Aceh as a place to find protein needs for the family; secondly, as a place to fulfill family needs; and thirdly, as a place to find support for the household; therefore, forests in the past were protected. The people of Aceh knew that if the forest were not well protected, all household needs would be lost. Today, Aceh's forests are starting to lose their luxury because there are many interests in these forests, both those of business groups, ruling groups, and ordinary people. There is a contestation of every interest; for the sake of interests that seek profit, they may ignore other interests; in this case, it is ignoring the interests and sustainability of Aceh's forests. The question of this article is, how was the Livig law that existed in the Acehnese used to protect the forest. Therefore, it is interesting to study the experiences of the Acehnese people in protecting forests. The research uses qualitative research with a non-doctrinal approach. The research results show three interests of forests for the people of Aceh, namely forests as a place for hunting deer, a place for gardening, and a place for hunting fish in rivers. Acehnese people used cultural, legal, and religious approaches to protect forests. These three approaches are related to each other. Education regarding these three approaches is not through formal education but through social institutions that exist in society